Conceptual and Generative Practices in Language based Artistic Research - Koutsomichalis, Marinos; Van den Berg, Marjolijn; Smith, Rachel; Hauner, Andrew; Roloff, Simon; Daus, Cordula (My University, 2021)
Contemporary artistic and avantgarde literary practice, especially where it belongs to the tradition of language based institutional critique, conceptual art and generative art is often based on procedures and methodic frameworks, sometimes to the extent that the process of development of an artwork will be indistinguishable from the work itself. These procedures are not reduced to, but can be developed in engagement with theoretical concepts from the Humanities, Natural Sciences or Life Sciences as well as be derived from scientific methods of research and academic modes of presentation of its findings. The resulting concepts, methods or algorithms won’t usually resemble strict scientific modes of the production of knowledge, but rather aim to be unique and irreducible practices of enlightening, critical or otherwise thought-provoking insight in confrontation with language as an artistic medium. This session will map affinities between very diverse practices of conceptual and generative production of knowledge in language based artistic research. The participants are to present extracts of their work and discuss how the concepts and methods involved are feeding into what they regard as their research process. In doing so, we will cover contextualized practices from performance art, sound art, artist book production and computer-generated art.
Keywords: Artistic research; Language